2022
DOI: 10.3390/jcm11051189
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and Evaluation of a Physician-Free, Real-Time On-Table Adaptive Radiotherapy (PF-ROAR) Workflow for the MRIdian MR-Guided LINAC

Abstract: With the implementation of MR-LINACs, real-time adaptive radiotherapy has become a possibility within the clinic. However, the process of adapting a patient’s plan is time consuming and often requires input from the entire clinical team, which translates to decreased throughput and limited patient access. In this study, the authors propose and simulate a workflow to address these inefficiencies in staffing and patient throughput. Two physicians, three radiation therapists (RTT), and a research fellow each adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Regarding an MR-Linac ATS workflow, Willigenburg et al analyzed RTT-derived prostate CTV and OAR delineations [13]. Different to our study, online contour adaptations performed by RTTs were Since the introduction of oMRgRT, some studies described the important role of RTTs for online treatment approaches [11,23,24]. Hales et al described a novel 'clinician-lite' prostate treatment adapt-toposition (ATP) MR-Linac workflow, with a prominent role for RTTs [23].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Regarding an MR-Linac ATS workflow, Willigenburg et al analyzed RTT-derived prostate CTV and OAR delineations [13]. Different to our study, online contour adaptations performed by RTTs were Since the introduction of oMRgRT, some studies described the important role of RTTs for online treatment approaches [11,23,24]. Hales et al described a novel 'clinician-lite' prostate treatment adapt-toposition (ATP) MR-Linac workflow, with a prominent role for RTTs [23].…”
Section: Discussionmentioning
confidence: 80%
“…Another study found DSCvalues over 0.96 for OAR recontouring by two ROs, three RTTs and one research fellow in 10 patients with pelvic tumor sites. Subsequent non-physician treatment plans were acceptable in only 91.25 %, but in 97.2 % if one complex case was excluded, leading to the conclusion that the most complex oMRgRT treatments might be excepted for RTT-led workflows [24].…”
Section: Discussionmentioning
confidence: 99%
“…This contouring assessment is also site, dose, and clinical scenario dependent which further limits a single approach for all scenarios. For example, there are suggestions of contouring all OARs within 2 cm of prostate targets or 1.5 cm superior to bladder targets [14] , [15] . For pancreas, machine-learning applications determined contouring extent (3 cm radial) for pancreatic stereotactic ART but was developed for a now obsolete MR-guided cobalt machine [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Centres globally are moving towards RT‐led treatment workflows, making the traditional RT role more specialised. 16 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%